2021
DOI: 10.1186/s12890-021-01394-w
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound score assessing the pulmonary edema in pediatric acute respiratory distress syndrome received continuous hemofiltration therapy: a prospective observational study

Abstract: Background Lung ultrasound score is a potential method for determining pulmonary edema in acute respiratory distress syndrome (ARDS). Continuous renal replacement therapy (CRRT) has become the preferred modality to manage fluid overload during ARDS. The aim of this study was to evaluate the value of lung ultrasound (LUS) score on assessing the effects of CRRT on pulmonary edema and pulmonary function in pediatric ARDS. Methods We conducted a prospe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…LUS score correlated with lung function variables (dynamic lung compliance and OI) and duration of MV. LUS score and oxygenation improved with CRRT, suggesting resolution of lung edema (69). Improving LUS score over time is associated with survival in patients with PARDS requiring extracorporeal membrane oxygenation (70).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LUS score correlated with lung function variables (dynamic lung compliance and OI) and duration of MV. LUS score and oxygenation improved with CRRT, suggesting resolution of lung edema (69). Improving LUS score over time is associated with survival in patients with PARDS requiring extracorporeal membrane oxygenation (70).…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have explored the potential role of these imaging tools. Wang et al (69) conducted a prospective cohort study using lung ultrasound (LUS) in patients with moderate to severe PARDS with half of them on continuous renal replacement therapy (CRRT). LUS score correlated with lung function variables (dynamic lung compliance and OI) and duration of MV.…”
Section: Justificationmentioning
confidence: 99%
“…LUS score has been recently demonstrated by Wang et. al 17 to correlate to lung function parameters in pediatrics acute respiratory distress syndrome such as dynamic lung compliance, oxygenation index and duration of mechanical ventilation. It was also demonstrated by Alencar et.…”
Section: Discussionmentioning
confidence: 99%
“…Increased EVLW leads to impaired gas exchange contributing to respiratory failure in ARDS. LUS score is a well-known non-invasive and repeatable method to assess EVLW in patients with ARDS ( 20 , 21 ), and LUS score is well correlated to the oxygenation status in both neonates and children ( 9 , 15 ). Systematic prospective multi-institutional studies indicated that EVLW is directly correlated to PaO 2 /FiO 2 and OI ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%